Transformation Mechanisms of Transition to the Model of “Green” Economy in Ukraine - BURLAKOVA, Iryna; KOVALOV, Bohdan; ŠAUER, Petr; DVOŘÁK, Antonín (Journal of Environmental Management and Tourism, 2018)
Within the last few years significant transformation changes in the direction of «green» growth in the Ukrainian economy on the background of a significant reduction in consumption and import of natural gas have been observed. The relevance of the study stems from the lack of conceptual clarity concerning mechanisms of the manageable transformational changes in the economy and forming an effective environment for further "green" growth. Based on systematic and synergetic approaches, the possible scenarios of transformation changes in the housing sector in Ukraine are drawn. The effective combination of negative and positive feedback mechanisms is found to contribute positively to ensure the needs of different population groups. The system-structural method is applied for developing conceptual basics of "green" economic model in Ukraine. The authors find that this is important to make the transition in Ukraine from the current "green" growth paradigm of separate sectors to the transformation changes generating a positive synergy between economic sectors. "Green" value chains management and partial localization of economic processes are preferred in the development of transformation mechanisms of the "green" economic model. Based on this empirical and theoretical review, the evaluation criteria of transformation changes in the sectoral, organizational and territorial structure of the economy are suggested.